Generation of a SARS-CoV-2-susceptible mouse model using adenovirus vector expressing human angiotensin-converting enzyme 2 driven by an elongation factor 1α promoter with leftward orientation - Matsumoto, Yusuke; Honda, Tomoko; Yasui, Fumihiko; Endo, Akinori; Sanada, Takahiro; Toyama, Sakiko; Takagi, Asako; Munakata, Tsubasa; Kono, Risa; Yamaji, Kenzaburo; Yamamoto, Naoki; Saeki, Yasushi; et al. (Frontiers in Immunology, 2024)
IntroductionTo analyze the molecular pathogenesis of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a small animal model such as mice is needed: human angiotensin converting enzyme 2 (hACE2), the receptor of SARS-CoV-2, needs to be expressed in the respiratory tract of mice.MethodsWe conferred SARS-CoV-2 susceptibility in mice by using an adenoviral vector expressing hACE2 driven by an elongation factor 1α (EF1α) promoter with a leftward orientation.ResultsIn this model, severe pneumonia like human COVID-19 was observed in SARS-CoV-2-infected mice, which was confirmed by dramatic infiltration of inflammatory cells in the lung with efficient viral replication. An early circulating strain of SARS-CoV-2 caused the most severe weight loss when compared to SARS-CoV-2 variants such as Alpha, Beta and Gamma, although histopathological findings, viral replication, and cytokine expression characteristics were comparableDiscussionWe found that a distinct proteome of an early circulating strain infected lung characterized by elevated complement activation and blood coagulation, which were mild in other variants, can contribute to disease severity. Unraveling the specificity of early circulating SARS-CoV-2 strains is important in elucidating the origin of the pandemic.